An antisymmetric, minimalist approach to Persian phrase structure. - Moinzadeh, Ahmad. (University of Ottawa (Canada), 2001)
In this thesis, I investigate phrase structure in Persian within the Minimalist framework of Chomsky (1995, 1998). Adopting Kayne's (1994) Linear Correspondence Axiom, which examines the relation of hierarchical structure and linear order, I propose a head-initial analysis for Persian, and develop an analysis of SVO word order based on the examination of all lexical and functional categories. Prior to investigating categories which are common to other languages, I examine the Ezafe Phrase (EzP), a functional phrasal category specific to Persian. The EzP is headed by a morpheme which may be phonetically realized as e/ye or null o. This morpheme regulates the occurrence of more than one complement in DPs/NPs and APs. Like the other phrasal categories investigated, the EzP is shown to follow the Spec-Head-Complement configuration (of the Linear Correspondence Axiom). My argumentation for a head-initial configuration for Persian, and the implication of a basic SVO word order is based largely on evidence for noun phrases and verb phrases. I provide support for a DP analysis of Persian nominal phrases, and demonstrate that both DPs and lexical NPs display a head-initial configuration. While Persian VPs exhibit both VO and OV word order in unmarked sentences, I argue that they consistently display a head-initial configuration, an analysis which is theoretically preferable to one based on dual directionality. I support my proposal for a head-initial analysis of VPs and a basic SVO word order in Persian with a variety of empirical evidence about verbal complements, including the exclusive post-verbal generation of CP complements, the placement of clitics, and the position of adverbs relative to verbal heads and their complements. While concentrating on DPs and VPs, I further support my analysis of a head-initial configuration for Persian by examining the Spec-Head-Complement configuration in APs, PPs, IPs and in less detail, the internal structure of CPs and TopPs. On the basis of both theoretical and empirical evidence, I propose a head-initial analysis for all phrasal categories in Persian. In conclusion, I turn to diachronic data which also provides evidence of the Spec-Head-Complement analysis I have proposed for Modern Persian.
Keywords: Language, Linguistics.